Cultivating Civic Virtue in Early Education: The Implementation of Pancasila Values in Primary School Students' Daily Behavior - Saepudin Karta Sasmita; Dini Handayani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The suboptimal implementation of Pancasila values among elementary school students, manifested in rising bullying, low discipline, and weak environmental responsibility, demands systemic investigation. This study examines how the five core Pancasila principles are integrated into students' daily behavior at a public primary school in South Tangerang City, while identifying key supporting and inhibiting factors. Employing a descriptive qualitative single case-study design, data was gathered over a four-week period via participant observation, structured teacher interviews, and extensive documentation. Analysis followed the classic Miles and Huberman framework (data reduction, display, and conclusion drawing), with trustworthiness rigorously ensured through source, technique, and time triangulation strategies. Findings reveal highly uneven implementation across the five principles: divinity values are most consistently practiced due to established daily routines, while unity and humanity values thrive primarily within structured activities. Conversely, democratic deliberation and social justice values weaken significantly once students operate outside direct teacher supervision. Crucial systemic facilitators include consistent teacher role-modeling, routine habituation, and active parental support. Meanwhile, primary barriers include a scarcity of explicit fairness-building activities, student over-dependence on external oversight, and unmonitored digital media influences. This study concludes that successful moral internalization depends heavily on sustained behavioral habituation rather than conceptual instruction alone, offering vital theoretical and practical implications for refining primary-level character-education policies.